1995
DOI: 10.1093/hmg/4.9.1551
|View full text |Cite
|
Sign up to set email alerts
|

Candidate regions for a testicular cancer susceptibility gene

Abstract: Epidemiological data suggest the presence of a susceptibility gene for testicular cancer in some families. Families with multiple cases of testicular cancer are rare and almost all those reported have only two affected members. We have performed a sib-pair analysis on 35 families in which there are either two or three affected brothers. These families have been typed for 220 autosomal microsatellite markers spaced 10-20 cM throughout the genome. Six regions which gave a LOD score of more than 1.0 on formal lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…However, if a single gene were involved then the magnitude of the increased risk to first-degree relatives indicates that such a gene should be readily mapped (Risch, 1990). In the first major effort to map such a gene, brothers with testicular cancer have been identified and sampled and then a genomic search was performed (Leahy et al, 1995). Evidence for a number of genetic regions has been shown but no one region is unequivocally the site of a testis cancer gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, if a single gene were involved then the magnitude of the increased risk to first-degree relatives indicates that such a gene should be readily mapped (Risch, 1990). In the first major effort to map such a gene, brothers with testicular cancer have been identified and sampled and then a genomic search was performed (Leahy et al, 1995). Evidence for a number of genetic regions has been shown but no one region is unequivocally the site of a testis cancer gene.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary linkage study of testicular cancer kindreds identiÂźed a number of candidate sites in the human genome, albeit at low LOD scores, including loci at D5S428 and D5S409 (International Testicular Cancer Linkage Consortium, 1998;Leahy et al, 1995). Interestingly, these are precisely the same markers that identify two of the three deleted regions in this study.…”
Section: Discussionmentioning
confidence: 53%
“…Although several candidate genes have been proposed, further research is indicated to clarify the molecular genetic basis and to identify the testicular cancer susceptibility gene(s) (Leahy et al, 1995;International Testicular Cancer Linkage Consortium, 1998;Murty and Chaganti, 1998). Individuals in stable founder populations share a relatively high frequency of genes from common ancestors, i.e.…”
Section: Discussionmentioning
confidence: 99%